Effect of Extractant-to-Semi Refined Carrageenan Water Ratio on the Physicochemical Characteristics of Carrageenan from Kappaphycus striatum: English - Alvianto, Dikianur; Lalu Danu Prima Arzani (AJARCDE (Asian Journal of Applied Research for Community Development and Empowerment), 2025)
Kappaphycus striatum, a red seaweed rich in sulfated polysaccharides, serves as a promising raw material for carrageenan production due to its favorable gelling and stabilizing properties. This study aimed to investigate the effect of different extractor solvent ratios on the physicochemical characteristics of refined carrageenan derived from K. striatum. Refined carrageenan was extracted from semi-refined material using hot water at solvent-to-seaweed ratios of 1:40, 1:50, and 1:60, followed by precipitation with isopropyl alcohol. The parameters assessed included moisture content, yield, gel strength, sulfate content, and viscosity. Moisture content remained relatively constant across treatments (?10–11%) and complied with FAO/JECFA standards. In contrast, yield and gel strength increased significantly with higher solvent ratios, with the highest values observed at the 1:60 ratio (30.04% yield; 1090.23 g/cm² gel strength). Sulfate content also increased, peaking at 21.42% for the same treatment. Viscosity was highest at the 1:50 ratio (87 cP), indicating a favorable balance between molecular hydration and structural integrity. All treatments produced carrageenan within acceptable quality standards for commercial use. The results demonstrated that the extraction solvent ratio played a critical role in determining the performance characteristics of refined carrageenan. Therefore, adjusting the water-to-seaweed ratio during extraction may serve as a practical approach to optimize carrageenan properties for targeted industrial applications.Contribution to Sustainable Development Goals (SDGs): SDG 1 :No povertySDG  9: Industry, Innovation and InfrastructureSDG 12: Responsible Consumption and ProductionSDG 14: Life Below Water